Wastewater treatment process: a modified mathematical model for oxidation ponds - Syafiqah Hanis, Mohd Fauzi; Norazaliza, Mohd Jamil (Akademi Baru, 2021)
Wastewater treatment aims to eliminate as many suspended solids as possible from the remaining water, known as effluent, before it is released into the environment. Pond oxidation methods have been practically proven successful for the wastewater treatment process because of their low construction and maintenance costs. This study aimed to investigate the degradation of wastewater pollutants through an oxidation pond treatment system. The purpose was to observe the relationship between the concentration of bacteria which are phototrophic and coliform, chemical oxygen demand (COD), and dissolved oxygen (DO). In this paper, a modified model consist of a set of an ordinary differential equation (ODE) has been developed by incorporating the Monod Equation. The model was solved numerically using the 4th order Runge Kutta method embedded in the MATLAB software. The root mean square error (RMSE) for the modified model was compared with the RMSE of the existing model. The results revealed that the modified model demonstrated a lower RMSE compared to the existing model. Thus, the modified mathematical model gives better result than the existing model. The model provides an excellent approximation for concentration needed for an oxidized pond to produce good water quality